2009
DOI: 10.1063/1.3067824
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely propagating ion acoustic solitary waves in magnetized dusty plasma in the presence of nonthermal electrons

Abstract: Obliquely propagating dust ion acoustic solitary waves subjected to an external magnetic field are studied using Sagdeev’s pseudopotential technique. Nonthermal distribution for electrons is considered. The pseudopotential is derived without considering the quasineutrality condition. It is obtained from the Poisson equation instead. Using Sagdeev’s technique, the ranges of parameters for which solitary waves exist are studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The linear theory was only valid when the amplitude of DIA was small, while the nonlinearity was not always neglected as the amplitude of the DIA waves were sufficiently large. The nonlinear propagation of the low-frequency DIA waves will give rise to solitary waves [12][13][14][15] or shock waves, [16][17][18] which were extensively studied by many authors during the past few years. In the magnetized dusty plasmas, the instability criterion and growth rate of the DIA waves depend on the external magnetic field and can be described by the Korteweg-de Vries ͑KdV͒ equation 12 or Kadomtsev-Petviashvili equation 13 or Zakharov-Kuznetsov equation 9 for the small amplitude DIA waves.…”
Section: The Effects Of Nonadiabatic Dust Charge Variation and Ultravmentioning
confidence: 99%
“…The linear theory was only valid when the amplitude of DIA was small, while the nonlinearity was not always neglected as the amplitude of the DIA waves were sufficiently large. The nonlinear propagation of the low-frequency DIA waves will give rise to solitary waves [12][13][14][15] or shock waves, [16][17][18] which were extensively studied by many authors during the past few years. In the magnetized dusty plasmas, the instability criterion and growth rate of the DIA waves depend on the external magnetic field and can be described by the Korteweg-de Vries ͑KdV͒ equation 12 or Kadomtsev-Petviashvili equation 13 or Zakharov-Kuznetsov equation 9 for the small amplitude DIA waves.…”
Section: The Effects Of Nonadiabatic Dust Charge Variation and Ultravmentioning
confidence: 99%
“…The first attempt which describes the energetic electrons observed by FREJA satellite using the nonthermal distribution was developed by Cairns et al 1995. Later, the existence of nonthermal electrons in various astrophysical environments, such as solar wind, magnetosphere, interstellar medium, and auroral zone plasmas (Cairns et al 1995;Saha and Chatterjee 2009;Mamun and Shukla 2009;Selim 2016;Lundin et al 1989;Futaana et al 2003;Gill et al 2007), was confirmed by the Vela satellite (Lundin et al 1989). Also, the disappearance of energetic electrons from the upper ionosphere of Mars has been recorded by the ASPERA on the Phobos 2 satellite.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, many space and laboratory observations indicate the existence of electrons with high energies that do not obey Boltzmann distribution. Instead, the distribution of electron energy, frequently has more complicated shapes with long tails, modeled by a nonthermal distribution (Cairns et al 1995;Saha and Chatterjee 2009;Mamun and Shukla 2009;Selim 2016). The first attempt which describes the energetic electrons observed by FREJA satellite using the nonthermal distribution was developed by Cairns et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, it has shown that electrons and ions do not only follow the isothermal Maxwellian distribution but also follow many other nonisothermal distributions, particularly, trapped or vortexlike distribution of Schamel 11 and nonthermal distribution of Cairns et al, 12 which are very important for interpreting many space and laboratory plasma situations. [13][14][15] A large number of authors [16][17][18][19][20] have used the vortexlike distribution of Schamel 11 or nonthermal distribution of Cairns et al 12 for calculating the electron or ion number densities in a dusty plasma, and have studied the linear and properties of the dust-electroacoustic waves and associated instabilities in dusty plasmas. However, many of them have taken the roles of the population of nonthermal or trapped electrons or ions in calculating electron or ion number densities, but completely ignored their contribution in dust charging currents.…”
Section: Introductionmentioning
confidence: 99%